Pemanfaatan Sampah Organik Rumah Tangga Menjadi Kompos Serbaguna di Desa Bakungtemenggungan Balongbendo Sidoarjo - Sakia Amanda Deviana Putri; Nur Sa’adatut Daraini; Anggi Windra Kusuma; Yeni Vitrianingsih; Uswatun Chasanah; Rahayu Mardikaningsih; Mirza Elmy Safira; Roidatus Shofiyah; Mila Hariani; Yuliastutik Yuliastutik; Nailul Ulah Al Chumairoh Machfud (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
The purpose of this community service program is to increase awareness and ability of local communities in handling organic waste from homes to be composted. Waste that can be used effectively to reduce environmental pollution and improve the condition of agricultural land is called household organic waste. The method used is participatory Action Research (PAR) this activity is in the form of a field demonstration which takes place at the Green House of Bakungtemenggungan village by directly showing the process of making liquid compost in the field. The results obtained in this activity show that the community has increased its ability in terms of handling organic waste and making compost which is one form of organic fertilizer. Community service activities, villagers can reduce the amount of waste that ends up in the environment and increase knowledge and ability in waste management.